Development of Problem Based Learning Teaching Modules Based on Blended Learning in the Implementation of the Independent Curriculum - Maulisa, Asra; Herliana, Fitria; Mahzum, Elmi; Elisa, Elisa; Farhan, Ahmad; Nurulwati, Nurulwati (MJI Publisher, 2024)
The implementation of the independent curriculum in the education system requires teachers to develop teaching modules while conducting instructional activities in the right direction. This research aims to develop a problem-based learning teaching module based on blended learning that is suitable for implementation within the context of the independent curriculum. The type of this research is Research and Development using the ADDIE development model, which stands for analysis, design, development, implementation, and evaluation. In this research, the implementation is limited to the development stage only. The suitability of the teaching module is measured through the validation results of the teaching module, as well as the responses from teachers and students. The subjects of this research are physics teachers and 11th-grade students at SMA Methodist Banda Aceh. Data collection techniques involve the validation questionnaire for the teaching module by experts and practitioners, as well as questionnaires to gather responses from teachers and students. The research data is then analyzed using quantitative descriptive methods with percentage techniques. The overall validation results of the teaching module by content experts indicate a score of 99.7%, construction experts at 91.5%, and practitioners at 90%, all falling under the category of highly valid. Additionally, the results from the teacher response questionnaire show a score of 90%, and the student response questionnaire indicates a score of 86%, both falling into the category of very good. Based on the research findings, it can be concluded that the development of a problem-based learning teaching module based on blended learning is suitable for implementation within the framework of the independent curriculum.